Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. Reality of applying transformational leadership in the school administration of the secondary school pathways system in Riyadh Mrs. Ameera Ayedh Al-Otaibi , Dr. Areej Makki Al-Juhani 2. The performance of principals of primary schools in western Riyadh for administrative tasks in the light of knowledge management processes from their point of view Mrs. Fatemah Mohammad Al Rafdh 3. Participative Leadership Role in Applying Professional Learning Communities in Secondary Schools in Al-Kharg Governorate Mrs. Nora Shnien Alanazi , Co-Prof. Zainab Awad Darwish 4. Education in the Gulf countries in the light of international indicators and the achievement of the fourth goal of sustainable development goals Mrs. Meaad Maish Salah Al-Harbi, Dr. Bader Al-badrni 5. The role of extra-curricular activities in consolidating the values of citizenship and ways of promoting it in post-primary government education in the Sultanate of Oman from the viewpoint of its specialists Dr. Nasser Abdullah Mahroos Al-Saiari 6. The Effectiveness of Extended Reality on Students’ Academic Performance and Motivation in Primary School Education: A Meta-Analysis (2019-2022) Mrs. Amal Yahya Alharbi, Mrs. Dina Mohammed Alazwari , Mrs. Kholod Kheled Almandeel , Dr. Leena Ahmad Alfarani 7. The level of depersonalization/derealization disorder (D.D.D) among refugees: A descriptive study of Syrian refugees in Mecca city in 2023 through some demographic variables Dr. Mohammad Ali bin Hasan